Transgenic plants as genetic models for studying functions of plant genes - A. V. Kochetov; V. K. Shumny (Вавиловский журнал генетики и селекции, 2016)
Transgenic plants are widely used for the investigation of functions of particular genes as well as for reconstruction of complex gene networks controlling plant morphology, biochemistry, and physiology during different development stages and in response to various external stimuli. Gene engineering instruments for the design of transgenic plants with either elevated or suppressed expression of target genes are discussed. Genetic constructs for protein synthesis or antisense RNA/self-complementary double-stranded RNA transcription are described. Transgenic plants with elevated or decreased levels of expression of S-like ribonucleases and decreased expression of the proline dehydrogenase gene are considered as examples. It was believed that S-like RNase functions concern mainly phosphate remobilization from senescent organs. However, expression patterns of some genes coding for S-like RNases were similar to some pathogen-responsive genes (both local and systemic induction after wounding or pathogen inoculation). In addition, some pathogenesis-related proteins (PR-4 family) possess RNase activity and can inhibit growth of pathogenic fungi. Investigation of transgenic plants revealed that high ribonuclease activity in apoplast correlated with increased resistance against tobacco mosaic virus. Thus, S-like RNases may have a new function as a part of the plant basal antiviral defense mechanism. Another set of transgenic plants bears an antisense suppressor of the proline dehydrogenase gene (PDH) constructed with an Arabidopsis target gene segment. Tobacco, maize and sunflower plants with this heterologous suppressor were characterized with a moderate decrease in PDH activity and a mild (1.5–3-fold) increase in the proline content under normal conditions. It was also found that these plants were more tolerant to various abiotic stresses (drought, NaCl, cold, toxic heavy metals), which may result from the protective proline effect early in exposure to stress, preventing the cellular gene expression machinery from damage by stress-generated free radicals.